Utilisation of Hospital Outpatient Services by Diabetes Mellitus Sufferers, Analysis of BPJS Kesehatan Sample Data - Nugraha, Erfan Chandra; Pujiyanto, Pujiyanto; Permanasari, Vetty Yulianty (BPJS Kesehatan, 2024)
Diabetes mellitus is a catastrophic disease that burdens the financing of the National Health Insurance or Jaminan Kesehatan Nasional Program, and sufferers continue to increase. Specific participant segments still widely use access for participants with diabetes mellitus to utilise health services at advanced-level referral health facilities. Various factors also influence access to health services at advanced-level referral health facilities. This research aims to analyse utilisation based on membership type and examine the factors that affect the utilisation of advanced outpatient services by JKN participants with DM. This research uses secondary data from the 2022 DM contextual BPJS Health sample data. The data was analysed univariately, bivariately, and multivariately with the Zero Inflated Negative Binomial regression model. The results of statistical tests showed that in outpatient care, age, type of participant, gender, treatment class, and province of participants were significantly different in terms of health service utilisation. The influence of the type of participation in the JKN program significantly affects the utilisation of services in outpatient care; the utilisation of non-recipients of contribution assistance participants is 1.16 times greater than that of the recipient of contribution assistance participants in outpatient care.